Rejection Sensitivity, Self-Compassion, and Aggressive Behavior: The Role of Borderline Features as a Mediator - Sommerfeld, Eliane (Front Psychol, 2020)
This study used mediation analyses to examine the assumption that the presence of borderline personality features mediates the relationship between rejection sensitivity (RS), self-compassion, and aggressive behavior. Sixty adults consisting of 31 participants diagnosed with borderline personality disorder and 29 participants with no diagnosis of borderline personality disorder were assessed for RS, self-compassion, aggressive behavior, and borderline personality features. Mediation was found for the total aggression score, anger score, and hostility score regarding both self-compassion and RS. Mediation was also found regarding RS and verbal and physical aggression, and regarding self-compassion and verbal and physical aggression. These findings provide evidence that the presence of borderline personality features is an important factor in explaining the associations linking RS and self-compassion to aggressive behavior. High RS and low self-compassion are associated with greater borderline personality features, which in turn relate to increased aggressive behavior.